Reconstruction of the Penal System Based on Triple Vulnerability: Harmonization of Lex Generalis and Lex Specialis in Handling Sexual Violence against Girls with Disabilities - Nurisnah, Nurisnah; Saputra, Asbudi Dwi; Muthia, Nuriyah Fara; Dahlan, Muhammad Fitratallah; Rivanie, Syarif Saddam (CV. Social Politic Genius (SIGn), 2025)
The escalation of sexual violence cases against girls with disabilities has reached a crisis stage, exacerbated by the fragmentation of legal regulations operating sectorally. The failure of the judicial system to respond to the complexity of victim vulnerability frequently creates impunity loopholes, perpetuating victimization practices. This research aims to analyze the legal anatomy of “triple vulnerability” and reconstruct the “Integrated Juridical Trident” model as a harmonization solution for the national penal system. Using a normative juridical research method with statute and conceptual approaches, this study examines the synchronization of norms among Law Number 1 of 2023, Law Number 20 of 2025, and related specific laws. The results prove that the intersection of child, female, and person with disabilities statuses constitutes a juridical determinant automatically triggering the application of the absolute rape offense and state accommodation obligations. The constructed trident model positions Law Number 1 of 2023 as the material legality foundation and Law Number 20 of 2025 as the formal legality foundation, synergized horizontally with Law Number 23 of 2002 as the subject determinant, Law Number 8 of 2016 as the procedural rights guarantor, and Law Number 12 of 2022 as the recovery guarantee. The effectiveness of this model is secured by a precision law enforcement strategy, through the validation of proof of equality between witnesses with disabilities and the application of an absolute prohibition on restorative justice. This study concludes that such system integration is necessary to close legal loopholes and guarantee maximum sentencing certainty for perpetrators of these crimes against humanity.